Geometric Morphometric Analysis of Sexual Dimorphism in the Bill of the White Stork (Ciconia ciconia) - Ebuderda Günay; Tomasz Szara; Buket Çakar; Emine İrem Deveci; Ali Serhan Coşkun; Gökhan Gün; Funda Yiğit; Ozan Gündemir; Sokol Duro; Mihaela Claudia Spataru (Animals)
Sexual dimorphism in bill morphology influences foraging strategies and bird competitive interactions. This study uses geometric morphometric analyses to examine sex-based differences in the bill shape and size of Ciconia ciconia, a large wading bird. Standardized dorsal and lateral photographs of 45 white storks (24 females and 21 males) were analyzed. The mean centroid size (CS) confirmed that males have significantly larger bills than females, yet principal component analysis revealed no reliable shape-based sex differentiation. Allometric analyses indicated that larger individuals exhibit more pronounced shape variations, likely tied to functional adaptations, though these were insufficient for sex determination. While bill size correlates with sex, shape variation does not serve as a reliable criterion for sexing C. ciconia. This study contributes to the understanding of sexual dimorphism in Ciconia ciconia by quantifying bill size differences using geometric morphometrics.